Phytochemical characterization and antioxidant profile of Sechium edule (Jacq) Swartz (Cucurbitaceae) varieties grown in Costa Rica - Jonathan Parra; Priscilla Hernández; Fernando Ocampo-Maroto; Víctor Álvarez-Valverde; Yendry Carvajal-Miranda; Gerardo Rodríguez-Rodríguez; Cristina Herrera (GarVal Editorial Ltda., 2018)
Context: The Sechium edule fruit is grown and consumed because of their nutritional values in different countries of Latin America. Costa Rica is one of the most important producers and exporters. It is consumed as an antioxidant because its flavonoid content suggests such activity; however, the selection of varieties to crop does not involve the phytochemical profile of them. Aims: To characterize the phytochemical and antioxidant profile of the S. edule varieties grown in Costa Rica. Methods: The in vitro radical scavenging activity of different S. edule extracts were measured using DPPH and ORAC assays, as well as their inhibition of lipid peroxidation in rat liver and their redox potential by cyclic voltammetry. Flavonoids glycosides were isolated by HPLC and their structures were determined by NMR. Results: The S. edule varieties grown in Costa Rica showed a good radical scavenging activity and inhibition of lipid peroxidation; there were significant differences between varieties. In addition, the redox potential determined by electrochemical methods suggested the presence of flavonoids, which was confirmed by the isolation of apigenin 7-O-rutinoside and luteolin 7-O-rutinoside. Conclusions: The antioxidant potential of varieties of S. edule grown in Costa Rica was confirmed, identifying the 845 variety as the best antioxidant profile.